Clinical case of mucocutaneous lymphonodular syndrome (Kawasaki disease) - I. A. Loginova; A. N. Bashlakova; A. A. Ustinovich; H. Y. Dolidovich; V. S. Khаtsko; T. G. Mozzhukhina; N. V. Sarkisyan; S. N. Pasynkova (Military Medicine, 2026)
Kawasaki syndrome (SC) is an acute systemic disease involving small and medium-sized arteries with the development of proliferative vasculitis. The main number of cases are children under 1 to 5 years of age, while the disease is extremely rare in children in the first months of life. Currently, there is an increase in IC all over the world. The problems of diagnosis of SC are associated with the rare occurrence and absence of pathognomonic symptoms and laboratory criteria of the disease, which leads to underdiagnosis of the latter. SC can pose a threat to the patient’s life and health not only in the acute period, but also after many years, which is associated with the risk of coronary artery aneurysms in patients who have not received adequate pathogenetic therapy, namely, the administration of intravenous immunoglobulins (IVIG). Meanwhile, timely diagnosis and administration of IVIG can reduce the risk of aneurysm formation from 25 % to 4 %. As is known, the presence of coronary artery aneurysms suggests life-threatening complications in the form of thrombosis and/or stenosis, which can lead to ischemia and sudden death at a young age. At the same time, the awareness of doctors of the therapeutic profile regarding the UK is insufficient. The article considers a case of Kawasaki disease in a three-month-old child, analyzes in detail the course of the pathological process.